2016
DOI: 10.1027/1864-9335/a000274
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulatory Processes in the Appraisal of Moral Courage Situations

Abstract: Abstract. The present research conceives of morally courageous behavior as goal-directed behavior and extends its investigation from a mere situational approach to a more comprehensive understanding including dispositional determinants related to self-regulatory processes. We tested the assumption that individual difference variables differentially affect the appraisal of the two core constituents of moral courage, namely, norm violation and risk of intervention. In two samples from different cultural (Switzer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…Above all, they know how to regulate their emotions, as evidenced by high correlations between the social control score and the cognitive reappraisal subscale. Given this last finding, one might even speculate that certain individuals speak up and express their opposition as a means to regulate their emotions: They witness an uncivil or immoral behaviour, they feel bad about it, and intervening causes them to reduce the negative emotions they are experiencing (see also Brandstätter, Jonas, Koletzko, & Fischer, ).…”
Section: Resultsmentioning
confidence: 99%
“…Above all, they know how to regulate their emotions, as evidenced by high correlations between the social control score and the cognitive reappraisal subscale. Given this last finding, one might even speculate that certain individuals speak up and express their opposition as a means to regulate their emotions: They witness an uncivil or immoral behaviour, they feel bad about it, and intervening causes them to reduce the negative emotions they are experiencing (see also Brandstätter, Jonas, Koletzko, & Fischer, ).…”
Section: Resultsmentioning
confidence: 99%
“…To do so, they consider moral principles and perform a correct act that is not easy to do [8]. Some studies have demonstrated that moral courage is related to concepts concerning assessment of ethics under certain conditions like sensitivity to justice [9], perception of control on one's emotions and performance such as emotional self-regulation [10], and selfefficacy [11]. Moral courage predisposes to performing ethical norms regardless of social costs [12], helping patients reduce symptoms of pain and agony, communicating effectively with patients and their families, and cooperating with physicians [13], inclination for recognizing others' sufferings and sensitivity to them, expression of sympathy and kindness, helping the needy, doing something to decrease others' pains and sufferings, and challenging the current situation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Among these moral concepts, moral courage has become subject to scientific inquiry in the last decade (Brandstätter et al 2016). Although there are several conceptions of this construct (Hannah et al 2011;Kidder 2005;Miller 2002;Osswald et al 2011;Serrat 2017), scholars define it as "acting correctly in the face of popular opposition, shame, scandal or discouragement" (Serrat 2017, p. 489).…”
Section: Moral Courage As a Key To Actmentioning
confidence: 99%